Contemporary Narratives of Ageing, Illness, Care - Sako, Katsura; Falcus, Sarah (Routledge Interdisciplinary Perspectives on Literature, 2022)
This collection of essays explores cultural narratives of care in the contexts of ageing and illness. It includes both text-based and practice-based contributions by leading and emerging scholars in humanistic studies of ageing. They consider care not only in film (feature and documentary) and literature (novel, short story, children's picturebook) but also in the fields of theatre performance, photography and music. The collection has a broad geographical scope with case studies and primary texts from Europe and North America but also from Hong Kong, Japan, Australia, Argentina and Mexico. The volume asks what care, autonomy and dependence may mean and how these may be inflected by social and cultural specificities. Ultimately, it invites us to reflect on our relations to others as we face the global and local challenges of both the pandemic and ageing societies.